Screendance in the Wake of Screened Dance: Moving Forward Through Interactive Video - Anderson, Callum (The International Journal of Screendance, 2021)
This paper argues that screendance has always had a potential for interactivity, looks specifically at interactive video, and tracks its history through video art and video games. Taking into account the higher volume of dance that is migrating to the screen as a result of the Coronavirus/Covid-19 pandemic, it also suggests a new term, screened dance, to differentiate those dances and dance events which otherwise would have been live and co-present. Bringing together a transmedia screendance work that unfolded on social media, and interactive narrative works currently available to stream on Netflix, I argue that the innovations and adaptation in the delivery of dance content due to lockdowns imposed by Covid-19, have provided an opportunity for the possibility of interactive screendance.